2023
DOI: 10.3171/2023.2.spine221019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Risk Analysis Index and the modified 5-factor frailty index in predicting 30-day morbidity and mortality after spine surgery

Abstract: OBJECTIVE Frailty’s role in preoperative risk assessment in spine surgery has increased in association with the increasing size of the aging population. However, previous frailty assessment tools have significant limitations. The aim of this study was to compare the predictive ability of the Risk Analysis Index (RAI) with the 5-factor modified frailty index (mFI-5) for postoperative spine surgery morbidity and mortality. METHODS Data were collected from the American College of Surgeons National Surgical Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Despite this the mFI-11, an extended, comorbidity-based frailty measure version of the mFI-5, is the most commonly reported frailty index, garnering considerable attention in the neurosurgery spine literature [ 6 ]. RAI is an alternative screening tool that evaluates a patient’s overall health status based on various factors, including age, functional dependence, and comorbidities.5,7 RAI offers several advantages, such as its ease of use and integration into clinical workflows [ 7 - 10 ]. Studies in the neurosurgery literature, encompassing a wide range of routinely performed procedures, such as spinal [ 7 ], cranial [ 10 ], and functional [ 8 , 9 ] surgeries, demonstrate that the RAI consistently exhibits superior discrimination compared to mFI-5, and greater patient age [ 7 - 10 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this the mFI-11, an extended, comorbidity-based frailty measure version of the mFI-5, is the most commonly reported frailty index, garnering considerable attention in the neurosurgery spine literature [ 6 ]. RAI is an alternative screening tool that evaluates a patient’s overall health status based on various factors, including age, functional dependence, and comorbidities.5,7 RAI offers several advantages, such as its ease of use and integration into clinical workflows [ 7 - 10 ]. Studies in the neurosurgery literature, encompassing a wide range of routinely performed procedures, such as spinal [ 7 ], cranial [ 10 ], and functional [ 8 , 9 ] surgeries, demonstrate that the RAI consistently exhibits superior discrimination compared to mFI-5, and greater patient age [ 7 - 10 ].…”
mentioning
confidence: 99%
“…RAI is an alternative screening tool that evaluates a patient’s overall health status based on various factors, including age, functional dependence, and comorbidities.5,7 RAI offers several advantages, such as its ease of use and integration into clinical workflows [ 7 - 10 ]. Studies in the neurosurgery literature, encompassing a wide range of routinely performed procedures, such as spinal [ 7 ], cranial [ 10 ], and functional [ 8 , 9 ] surgeries, demonstrate that the RAI consistently exhibits superior discrimination compared to mFI-5, and greater patient age [ 7 - 10 ]. Moreover, in these studies the RAI has been shown to be more effective in predicting a wide variety of adverse outcomes [ 7 - 10 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbidities also impact nutritional status and loss of skeletal muscle mass. For this study, we classified comorbidity using the Modified Frailty Index 31,40-42 . Sarcopenia and loss of skeletal muscle mass were not associated with frailty in this study.…”
Section: Discussionmentioning
confidence: 99%
“…6,[11][12][13][14] It underscores the importance of using frailty assessment tools that are appropriate for the context and have been rigorously validated, such as the Risk Analysis Index, which has shown strong discriminatory accuracy in predicting surgical outcomes across various age groups. [15][16][17] The authors also present a brief comparison of frailty scores based on the 10 core principles defined in Table 4 that offers comparison for these tools. 6 However, a more comprehensive exposition is warranted, and a balanced comparison of the limitations inherent in both Risk Analysis Index and HFRS and other alternate risk scores should be undertaken to attain consensus within the field for a tool with most accurate predictability and better utilization across practice settings for risk-stratification and intervention decisions of our patients.…”
mentioning
confidence: 99%